Dirac versus Wigner : towards a universal particle concept in local quantum field theory - Detlev Buchholz and Martin Porrmann and Ulrich Stein (Physics letters. B, 1991)
Based on the concept of particle weight a unified description of stable particle-like systems in local quantum field theory is given which applies also to so called infraparticles. Particle weights carry definite charge, four momentum and spin and give rise to characteristic mass shell singularities. A collision theory for these weights is proposed which allows to calculate transition probabilities directly from local gauge invariant operators.